Implementação do processo de gestão de compliance em uma operadora de planos de saúde e prestadora de serviços de saúde - Sperafico, João Henrique (Universidade do Vale do Rio dos Sinos, 2016)
Compliance management is presented as a practice of managing the compliance of organizations, mainly regarding legal issues and ethical conduct. Considering the current ethical scandals in Brazil, the increase in health regulations and inspections makes it relevant to structure a compliance management process in companies. In this way, this work proposes to develop a project plan for the implementation of compliance management at Unimed Vale do Sinos. The project is aligned with the values of the organization, especially Ethics. The project provides to view the organization of a process of prevention, detection and correction of non-conforming situations from the identification of external requirements (laws, regulations) and internal requirements (organizational processes). For this, a feasibility study and project planning is required through the project management knowledge areas established in the PMBOK, concluding with the lessons learned stage.
Keywords: Plano de gerenciamento; Projeto; Compliance; Processos; Ética; Management plan; Project; Compliance; Process; Ethic